Everyday resistance in the Yin space-tracing queer heterotopias in Body2Body: A Malaysian Queer Anthology (2009) - Seach, Jin Beng (Penerbit Universiti Kebangsaan Malaysia, 2025)
Foucault’s concept of heterotopia refers to a space of resistance situated in the realm of in-betweenness, where alternative forms of existence become possible. In relation to the LGBTQ community, this notion has been recontextualised into queer heterotopia, a space that enables LGBTQ individuals to live without conforming to heteronormative standards. This study examines queer heterotopia in Malaysian queer literature through selected short stories in Body2Body: A Malaysian Queer Anthology (2009), while also incorporating the Chinese metaphysical concept of yin–yang. It argues that queer heterotopia cannot emerge independently; rather, it is preceded and sustained by a yin-inclined space associated with femininity, darkness, fluidity, and secrecy. For characters living on the margins, the yin space provides the conditions necessary to form resistance. Within the anthology, queer characters navigating hostile environments draw on yin energy to reach queer heterotopias, where they articulate their identities through performative, emotive, and sexual expressions as forms of everyday resistance. The findings suggest that resistance within queer heterotopia need not be overt or confrontational; even when subtle and nuanced, resistance rooted in the yin space remains empowering, prompting characters to assert meaningful agency in their existence.